Sintesis CeVO4 Menggunakan Metode Sol Gel dengan Ekstrak Daun Kasingsat (Senna occidentalis (L.) Link): Karakterisasi dan Aktivitas Fotokatalitik pada Iradiasi Cahaya Tampak - Eka Mardika Handayani; Muryanto Muryanto; Oman Zuas; Yoki Yulizar (Postgraduate, University of Mataram, 2022)
CeVO4 as visible light driven photocatalyst was synthesized using Senna occidentalis (L.) Link leaves extract (SOE) by sol-gel method which can increase the degradation of malachite green (MG) under visible irradiation. The products were characterized using Fourier Transform Infrared Spectrophotometer (FTIR), X-ray Diffraction (XRD), and Field Emission Scanning Electron Microscope Energy Dispersive Spectroscopy (FESEM-EDS). UV–Vis Diffuse Reflectance Spectrophotometer (UV–Vis DRS) absorption spectrum indicated that the band gap of the CeVO4 is about 2,76 eV, and XRD patterns of the samples were indexed to tetragonal zircon type CeVO4 structure. Photocatalytic activity of the synthesized CeVO4 nanoparticles was evaluated for degrading the MG under visible light irradiation, showing as an active catalyst on photodegradation of the MG up to 77% under experimental condition of this study.